Human papillomavirus testing as an optional screening tool in low-resource settings of Latin America: experience from the Latin American Screening study. Issue 3 (1st April 2006) - Longatto-Filho, A.; Eržen, M.; Branca, M.; Roteli-Martins, C.; Naud, P.; Derchain, S. F.M.; Hammes, L.; Sarian, L. O.; Bragança, J. F.; Matos, J.; Gontijo, R.; Lima, T.; et al.
Abstract : Hybrid capture II (HC II) test for oncogenic human papillomaviruses (HPV) was carried out in a cohort of 4284 women at their first clinical visit. Overall prevalence of HPV was 17.1%, decreasing with age from 33.9% among women below 20 years to only 11.0% among those older than 41 years. HPV prevalence was significantly higher among current smokers (odds ratio [OR] = 1.31; 95% CI 1.1–1.6), in women with two or more lifetime sexual partners (OR = 1.9; 95% CI 1.6–2.4), and those women with two or more sexual partners during the past 12 months prior to examination (OR = 1.6; 95% CI 1.2–2.2). HPV detection increased in parallel with increasing cytologic abnormality, being highest in women with high-grade squamous intraepithelial lesion ( P = 0.001). Specificity of the HPV test in detecting histologically confirmed cervical disease was 85% (95% CI 83.9–86.1). Sensitivity of the HPV test in detecting histologic abnormalities increased in parallel with disease severity, ranging from 51.5% for cervical intraepithelial neoplasia (CIN) 1 to 96.5% for CIN 3 and 100.0% for cancer, with respective decline of positive predictive value. These data suggest that HPV testing with HC II assay might be a viable screening tool among this population with relatively high prevalence of cervical disease.